SINISME DALAM KABA SABAI NAN ALUIH SUATU BENTUK PENTINGNYA BAHASA BAHASA IBU : KAJIAN PRAGMATIK - Rahmat, M.Hum, Wahyudi (Jurnal Curricula, 2017)
This paper discusses the establishment preservation mother tongue (language Minangkabau) in West Sumatra, especially in literature. This study reveals the cynicism narrative form in Kaba Sabai Nan Aluih. Use of cynicism in Kaba Sabai Nan Aluih someone speaking a form of expression. Cynicism is a statement that ridicule or scorn. This research was qualitative descriptive motde. The data collection method that is listening to refer to written language use and analysis using method Agih read many techniques. The results of this study indicate that there is some form of speech sinsime figure in Kaba Sabai Nan Aluih with the function of cynicism in the tale this is to add to the effect of aesthetic, resulting figure of speech in the form of satire in the form of doubts containing ridicule roughly and also learning the importance of mother tongue to be maintained if the study it is in the form of coarse satire in Minangkabau language.